A new directionality tool for assessing microtubule pattern alterations. Issue 4 (14th February 2014) - Liu, Wenhua; Ralston, Evelyn
<x xml:space="preserve">Abstract</x> The cytoskeleton (microtubules, actin and intermediate filaments) has a cell type‐specific spatial organization that is essential and reflects cell health. We are interested in understanding how changes in the organization of microtubules contribute to muscle diseases such as Duchenne muscular dystrophy (DMD). The grid‐like immunofluorescence microtubule pattern of fast‐twitch muscle fibers lends itself well to visual assessment. The more complicated pattern of other fibers does not. Furthermore, visual assessment is not quantitative. Therefore we have developed a robust software program for detecting and quantitating microtubule directionality. Such a tool was necessary because existing methods focus mainly on local image features and are not well suited for microtubules. Our tool, texture detection technique (TeDT), is based on the Haralick texture method and takes into account both local and global features with more weight on the latter. The results are expressed in a graphic form responsive to subtle variations in microtubule distribution, while a numerical score allows quantitation of directionality. Furthermore, the results are not affected by imaging conditions or post‐imaging procedures. TeDT successfully assesses test images and microtubules in fast‐twitch fibers of wild‐type and mdx mice (a model for DMD); TeDT also identifies and quantitates microtubule directionality in slow‐twitch fibers, in the fibers of young animals, and in other mouse models which could not be assessed visually. TeDT might also contribute to directionality assessments of other cytoskeletal components. Published 2014 Wiley Periodicals Inc. This article is a US government work and, as such, is in the public domain in the United States of America.